Utilizing untapped potential of rice fallow of East and North-east India through pulse production - Singh, N. P.; Praharaj, C. S.; Sandhu, J. S. (The Indian Journal of Genetics and Plant Breeding, 2017)
Rainfed areas of the country- characterized by its complexnature, diverse and fragile ecosystem and distress proneproduction system - play a key role in country’s foodproduction and economy. It is estimated that about 11.695m ha in India remains fallow after rice harvest, of whicharound 82% lies in the Eastern India and the rest falls inthree southern states viz., Tamil Nadu, Karnataka andAndhra Pradesh. These areas have a vast potential tocultivate low input and low water requiring upland pulsecrops (such as lentil, chickpea, lathyrus, mungbean andurdbean). However, depletion of soil moisture contentfollowing rice harvest affects timely sowing and receivingin of poor returns out of these ecosystems. Lack of lifesaving/supplementary irrigation at critical stages causesfurther soil moisture scarcity and hampers plant growthand crop productivity per se. Conservation agriculturethrough zero tillage, crop residue retention and crop rotationinvolving suitable genotypes influence pulses crop inrotation after rice. Two cropping systems viz., relay croppingof pulses in standing rice, and crop rotation after harvestof rice have potential for popularization and adoptiondepending on agro-ecosystem involved. Yet, theseconstrained areas require an understanding of ecology,constraints analysis and situation specific remedies.Keeping these facts, some potential managementconsiderations involving suitable pulses varieties, zerotillage, relay cropping, residue retention, mulching, seedpriming, life saving irrigations and foliar sprays of nutrientswere suggested that could help in improving pulsesproductivity under challenging rice fallow conditions.